2002
DOI: 10.1260/147547202765275970
|View full text |Cite
|
Sign up to set email alerts
|

Oscillation of Impinging Jet with Generation of Acoustic Waves

Abstract: This paper presents an oscillatory phenomenon of the underexpanded jet which issues from a convergent nozzle and impinges on a flat plate perpendicularly. As the characteristics of the generating noise deeply depend on the oscillation of the impinging jet, the flow field is visualized using the shadowgraph method and the pressure on the plate is measured to classify the oscillation modes for different parameters such as the nozzle pressure ratio and the distance between the nozzle and the plate. For the compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Given the aeroacoustic nature of the loop, it seems appropriate to use unsteady compressible simulations, which provide simultaneously all flow and acoustic variables and which have made spectacular progress over the last two decades. The axially symmetric or three-dimensional (3-D) Euler equations have for instance been solved by Sakakibara & Iwamoto (2002) in order to study the oscillatory phenomenon of an underexpanded jet impinging on a flat plate perpendicularly. Similarly, Kim & Park (2005) and Loh (2005) carried out simulations using the axisymmetric Navier-Stokes equations.…”
Section: Introductionmentioning
confidence: 99%
“…Given the aeroacoustic nature of the loop, it seems appropriate to use unsteady compressible simulations, which provide simultaneously all flow and acoustic variables and which have made spectacular progress over the last two decades. The axially symmetric or three-dimensional (3-D) Euler equations have for instance been solved by Sakakibara & Iwamoto (2002) in order to study the oscillatory phenomenon of an underexpanded jet impinging on a flat plate perpendicularly. Similarly, Kim & Park (2005) and Loh (2005) carried out simulations using the axisymmetric Navier-Stokes equations.…”
Section: Introductionmentioning
confidence: 99%
“…This makes difficult to capture the time resolution of the sound field. Bogey et al, [ 15 ] Shur et al, [ 16 ] Uzun et al, [ 17 ] Rubel, [ 18 ] Zhang et al, [ 19 ] and Modak et al [ 20 ] have studied the flow, whereas Sakakibara and Iwamoto, [ 21 ] Dhamanekar and Srinivasan, [ 22 ] Mankbadi et al, [ 23 ] Nonomura et al, [ 24 ] and Brehm et al [ 25 ] have reported on aspects related to the acoustic noise of the single impinging jet. They have demonstrated that the nozzle geometry, impact height, impact angle, and Reynolds number affect the characteristics of the acoustic source as well as the sound propagation.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical as well as both experimental and numerical simulations of unsteady impinging jets have also been carried out. Among them, some investigations involved in studying the self-induced oscillation [14], instabilities [15,16], modes of oscillation [17], near-field noise [18], TVD simulations [3], [19] to study the oscillations and generation of acoustic waves, Large Eddy Simulation [20], flow behavior coaxial impinging jets [21], etc. Recently, Yaga et al [22] conducted 3D investigations on the flow characteristics of rectangular under-expanded impinging jets both experimentally and numerically.…”
Section: Introductionmentioning
confidence: 99%